Shiv’im Shanah dan Koach Gvurot : Studi Hermeneutik tentang Kefanaan Manusia dalam Mazmur 90:10 - Wennar Wennar; Yohanes Rahdianto Suprandono (Universitas Methodist Indonesia, 2024)
This study examines Psalm 90:10 through a hermeneutic approach to understand the phrases